2011
DOI: 10.5505/tjtes.2011.15483
|View full text |Cite
|
Sign up to set email alerts
|

The effects on complications and myopathy of different voltages in electrical injuries

Abstract: AMAÇBu çalışmanın amacı, elektrik çarpmalarının demografik ve klinik özelliklerinin, laboratuvar bulgularının, komplikasyonların ve yaralanmalara bağlı mortalite, morbidite oranlarının araştırılmasıdır. GEREÇ VE YÖNTEMOcak 2006-Ocak 2010 tarihleri arasında elektrik çarpması nedeniyle acil servise başvuran olgular geriye dönük olarak incelendi. Olgular yaş, cinsiyet, elektrik kaynağının gücü (düşük-yüksek voltaj), mevsimsel dağılım, EKG değişiklik-leri, laboratuvar sonuçları, takip edildiği klinikler, komplikas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
1
10
0
2
Order By: Relevance
“…[13] Similarly, the rate of highvoltage burns in the present study was 50%, and the rate of low-voltage burns 44.7% (while the rate of flash burns was 5.3%). High-voltage electricity burns cause more serious tissue damage due to the high amounts of energy exerted.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…[13] Similarly, the rate of highvoltage burns in the present study was 50%, and the rate of low-voltage burns 44.7% (while the rate of flash burns was 5.3%). High-voltage electricity burns cause more serious tissue damage due to the high amounts of energy exerted.…”
Section: Discussionsupporting
confidence: 67%
“…[14,15] Mean patient age was reported as 30.2 or 25 years in a majority of studies. [13,16,17] Mean age in the present study was 18.8 years in females and 27.4 years in males. It was presently determined that mean TBSA was 11.9% in cases of low-voltage burns, and 21.8% in those of high voltage.…”
Section: Discussionmentioning
confidence: 49%
“…Arrowsmith et al (15) stated that ECG changes were present in 3% of the patients in their study. In the study conducted by Karadaş et al (16), ECG abnormalities were identified in 29.3% of the patients. In our study, similar to medical literature, the results of the evaluations of the 24-hour ECG monitoring showed that ECG changes were present in 19 (27.1%) of the patients at various time points.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Karadaş et al (16) identified ECG changes in only 8.9% of low-voltage EIs. Rai et al (26) identified ECG changes secondary to shock or arrhythmia in seven of 58 patients with high-voltage EIs.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Particularly, cardiac damage of electrical current may be dramatic and may cause mortality. [2,3] Electrocardiography (ECG) is an important diagnostic tool for arrhythmias and is obtained in all patients with EI. However, the effect of EI on ECG parameters has not been investigated in detail.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%